Coupling of magneto-strictive FeGa film with single-crystal diamond MEMS resonator for high-reliability magnetic sensing at high temperatures. Issue 5 (3rd May 2020) - Zhang, Zilong; Wu, Yuanzhao; Sang, Liwen; Wu, Haihua; Huang, Jian; Wang, Linjun; Takahashi, Yukiko; Li, Runwei; Koizumi, Satoshi; Toda, Masaya; Akita, Indianto Mohammad; Koide, Yasuo; et al.
ABSTRACT: Micro-electromechanical systems (MEMS) magnetic sensing at high temperatures over 573 K has not been achieved due to the difficulty in designing the rational interface with strong coupling. Here, a magnetic sensor based on FeGa/single-crystal diamond (SCD) MEMS resonator is realized to circumvent the challenges in magnetic sensing. The present magnetic sensor exhibits a stable high-sensitivity of 7.3 Hz/mT at 573 K and an experimental noise level of 4nT/√Hz. The performance exceeds those of reported high-temperature magnetic sensors. This work offers a strategy for developing magnetic sensors with merits super to the existing ones. GRAPHICAL ABSTRACT: Abstract : IMPACT STATEMENT The first high-temperature MEMS magnetic sensor over 573 K super to the present ones is realized by coupling a magneto-strictive FeGa film with a diamond MEMS resonator.